Rancang Bangun Aplikasi Web Pada Toko Reparasi Jaya Menggunakan Metode Prototype - Lestari, Ade Ayu Dini Dwiputri; Kartini, Kartini (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2023)
Jaya Repair Shop is a service provider of repair and maintenance of damaged or dirty footwear. Customers who want to repair their damaged footwear can only be served at the store location. Recording of orders is also still done manually using books. Information on available services and the amount of service fees can also only be known to customers by asking directly to the service provider. Similarly, the estimated repair time that cannot be ascertained often makes customers have to wait. Therefore, the author wants to design a web-based repair service ordering application to improve service and revenue Jaya Repair Shop. The system will be designed using prototype method and problem analysis using qualitative method described with fishbone diagram. The system will be built using PHP programming language and MySQL database. The result of this research is a web application for ordering shoe repair services that can be used by customers to order repair services anytime and anywhere, as well as a container to increase the income of repair service providers.